2001
DOI: 10.1038/sj.bjp.0704389
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐5 in growth and differentiation of blood eosinophil progenitors in asthma: effect of glucocorticoids

Abstract: 1 There are increased numbers of circulating CD34 + progenitor cells for eosinophils in patients with atopic asthma, with a further increase following allergen exposure or spontaneous worsening of asthma. We investigated the expression of IL-5 and IL-5Ra receptor in circulating CD34 + progenitor cells in allergic asthmatics and the eects of corticosteroids. 2 Using double-staining techniques, up to 50% of CD34 + cells expressed intracellular IL-5, and by RT ± PCR, there was signi®cant expression of IL-5 mRNA. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…31 Furthermore, BALf CD34 ϩ cells release quite high amounts of IL-5, suggesting that these cells have autocrine multiplication and/or differentiation pathways, which is in line with a previously suggested autocrine differentiation pathway of peripheral blood CD34 ϩ cells in individuals with asthma. 19 In conclusion, our study shows that AW allergen exposure induces an increase in early CD135 ϩ bone marrow hematopoietic progenitors without a simultaneous increase of the total number of bone marrow CD34 ϩ cells. In addition, allergen exposure increases the number of CD34 ϩ cells in BALf, and these CD34 ϩ cells not only can complete their differentiation into eosinophils but also have the capacity to produce eosinophil colonies, proving their ability to multiply.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…31 Furthermore, BALf CD34 ϩ cells release quite high amounts of IL-5, suggesting that these cells have autocrine multiplication and/or differentiation pathways, which is in line with a previously suggested autocrine differentiation pathway of peripheral blood CD34 ϩ cells in individuals with asthma. 19 In conclusion, our study shows that AW allergen exposure induces an increase in early CD135 ϩ bone marrow hematopoietic progenitors without a simultaneous increase of the total number of bone marrow CD34 ϩ cells. In addition, allergen exposure increases the number of CD34 ϩ cells in BALf, and these CD34 ϩ cells not only can complete their differentiation into eosinophils but also have the capacity to produce eosinophil colonies, proving their ability to multiply.…”
Section: Discussionmentioning
confidence: 52%
“…Following 8 and 14 days in culture, colonies contained more than 40 cells were counted by using an inverted light microscope as described previously. 19 To confirm the identification of eosinophil colonies on day 14, cells were washed with prewarmed RPMI medium supplied with 0.5% BSA and 20% FCS; cytospins were made and stained by the May-Grünwald-Giemsa method for differential cell counting. In addition, immunocytochemistry for CD34 antigen was performed together with LFB counterstaining and immunocytochemistry for IL-5R␣.…”
Section: Org Frommentioning
confidence: 99%
“…Both studies differ from our own, where recombinant IL-5 was present. More recently, Kuo et al have shown that dexamethasone decreases IL-5 mRNA and protein in human circulating CD34+ eosinophil progenitors, but does not decrease expression of IL-5Ra on these cells [36]. In their study, dexamethasone only decreased eosinophil colony formation by CD34+ cells from asthmatic donors.…”
Section: Discussionmentioning
confidence: 94%
“…Likewise, in a proof-of-concept study for the development of anti-IL-5 therapies (see below) in human subjects, systemically administered IL-5 stimulated the appearance of increased numbers of circulating CD34 þ /IL-5Ra þ cells. 67 In addition, several groups have reported the increased expression of IL-5Ra on CD34 þ progenitor cells in the bone marrow of atopic asthmatics. 68 This supports the concept that HSPCs in atopic subjects are primed to respond to IL-5 (ref.…”
Section: Ish and Allergic Inflammationmentioning
confidence: 99%
“…76,77 It has been shown that up to 50% of CD34 þ cells from asthmatic subjects express intracellular IL-5 protein and exhibit high expression of IL-5 mRNA. 67 Further, progeny of Eo/B progenitors in colonies express GM-CSF protein and mRNA, 82 and there is an autocrine GM-CSF-dependent signaling mechanism for Eo/B differentiation mediated through bacterial lipopolysaccharide signaling. 83 In addition, as CD34 þ progenitors undergo ISH in the nasal mucosa of allergic subjects, 59 IL-5, along with IL-9 signaling, can upregulate the surface expression of IL-5Ra during terminal eosinophil differentiation.…”
Section: Cytokines and Growth Factors That Influence Ishmentioning
confidence: 99%